Creators of Graffiti. Reflections on the Sociological Approach to the Graffiti Phenomenon - Gaubert, Aymeric (Huarte de San Juan. Geografía e Historia, 2024)
Graffiti is now a well-known document for its scientific interest and is the subject of a growing science: graffitology. It refers to an ancient and complex phenomenon which is characterised by a diversity of natures, functions, contexts and authors. Because of this plurality, it is a matter of questioning the existence of a sociodifferentiated use of walls in history, beyond any specific corpus. To do so, I suggest a reflection and an assessment on the sociological approach of graffiti makers, while questioning the method, the issues and the limits of such an endeavour. Recent historiographical contributions point to a multiple practice that goes beyond social, economic and cultural affiliations and invite us to reconsider the sociological extent of graffiti and its place in past and present societies. As sociocultural objects and direct testimonies, graffiti give voice to ordinary people as well as elites, to the popular masses as well as to the wordless, to the illiterate as well as to the literate.
Keywords: graffiti; graffitologie; archéologie de la trace; approche sociologique; anthropologie